Multiplicación de polinomios

Ejercicio 5º resuelto

Multiplicar:

1(x4 − 2x2 + 2) · (x2 − 2x + 3) =

= x 6 − 2x5 + 3x4 − 2x4 + 4x3 − 6x2 + 2x2 − 4x + 6=

= x 6 − 2x5 − 2x4 + 3x4 + 4x3 + 2x2 − 6x2 − 4x + 6 =

= x 6 −2x5 + x4 + 4x3 − 4x2 − 4x + 6

2 (3x2 − 5x) · (2x3 + 4x2 − x + 2) =

= 6x5 + 12x4 − 3x3 + 6x2 − 10x4 − 20x3 + 5x2 − 10x =

= 6x5 + 12x4 − 10x4 − 3x3 − 20x3 + 6x2 + 5x2 − 10x =

= 6x5 + 2x4 − 23x3 + 11x2 − 10x

3(2x2 − 5x + 6) · (3x4 − 5 x3 − 6 x2 + 4x − 3) =

= 6x6 − 10x5 − 12x4 + 8x3 − 6x2

− 15x5 + 25x4 + 30x3 − 20x2 + 15x +

+18x4 − 30x3 − 36x2 + 24x − 18 =

= 6x6 − 10x5 − 15x5 − 12x4 + 25x4 + 18x4 +

+8x3 − 30x3 + 30x3 − 6x2− 20x2 − 36x2 + 15x + 24x − 18 =

= 6x6 − 25x5 + 31x4 + 8x3 − 62x2 + 39x − 18